Manic Pseudo-Delirium–Two Case Reports - Gerard Hutchinson; Anthony David (Behavioural Neurology)
We wish to report two cases which illustrate a subtype of bipolar affective disorder and suggest that it should be termed Manic Pseudo-Delirium (MP-D) as it incorporates features of both mania and delirium. This will facilitate consistent recognition and characterization since mania remains the primary diagnosis and delirium is not thought to co-exist with functional psychoses. Extensive investigations were done to exclude underlying medical causes for the delirium. Possible explanations for MP-D are put forward for their heuristic value in the hope that further research will improve understanding of the pathophysiology of both mania and delirium.